Opportunities of and threats to consumer well-being in the age of Fourth Industrial Revolution (IR 4.0) technologies. Issue 1 (30th December 2021) - Boninsegni, Melanie Florence; Roy, Abhijit; Bakpayev, Marat; Kumar, Smriti; Peronard, Jean-Paul; Reimer, Thomas
Abstract : Purpose: Fourth Industrial Revolution (IR 4.0) technologies have strong potential to affect consumer well-being, positively or negatively, so the current paper aims to review potential opportunities and threats that these technologies represent for consumers in several core economic sectors: health care, education, financial services, manufacturing and retailing. Design/methodology/approach: This paper proposes a conceptual framework for how IR 4.0 technologies affect consumer well-being in five representative sectors: health care, education, financial services, manufacturing and retailing. The authors argue that the potential transformations of these specific sectors, facilitated by these technologies, may have profound effects on consumer well-being, with urgent public policy implications. Findings: Emerging technologies, such as artificial intelligence, robotics, the Internet of Things, three-dimensional printing, machine learning and blockchain, provide customers with novel approaches toward decisions regarding health, education, finances and other fundamental parts of their lives. The organizations that provide these services, such as hospitals, universities and banks, actively adopt the innovations offered by IR 4.0. These evolving and disruptive technologies thus are changing reality for consumers and providers. Originality/value: This paper proposes some novel public policy implications of IR 4.0 technologies for consumer well-being, and it outlines further research directions that can enhance understanding of relevant technologies and the consequences of their use for society.